Mothers and fathers' experiences of high conflict past two years post separation: A systematic review of the qualitative literature. Issue 2 (3rd April 2019) - Francia, Leanne; Millear, Prudence; Sharman, Rachael
Abstract: Within a child custody context, this article systematically reviewed the available qualitative research of post separation, high conflict, co-parenting relationships. Separated parents' experiences of high conflict were reportedly embedded in pervasive mistrust and disdain, and underpinned by concerns over differing parenting styles, or the other parent's ability to adequately care for the child. The factors that potentially maintained conflict were parental concerns regarding the child's safety and well-being when in the care of the other parent. The factor that potentially escalated conflict was disdain directed at the other parent's concerns. Recommendations for future research and implications for social policy for these families are discussed.